UJI ANTIOKSIDAN JAMU MADURA â€œEMPOT SUPERâ€ - Holil, kholifah (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2015)
Â The purpose of this research is to present scientific information related to maduraâ€™s herbal medicine â€œempot superâ€ and herbal extract made from existing composition of the various constituent plants of empot super. Then, this research spesifically detects antioxidants activity found in herbal medicine and herbal extract expected to provide a scientific assurance either for the industry or the consumen.Samples used in this research are maduraâ€™s herbal medicine and herbal extract mixture of various simplisia those are used in the manufacture of empot super herbal medicine. To get those samples, herbal medicine is imported from madura, while the herbal extract is the production of extraction process by using ethanol. The samples are subsequently assay the antioxidants activity by using DPPH method at 571nm.The final result of this research indicates the existance of IC50 proportion in herbal medicine that is 34,11mg/ml and 45,44mg/ml in herbal extract. Indeed, in the assay of herbal medicine and herbal extract classified as having a very strong antioxidants activity